Transverse Spurious Mode Compensation for AlN Lamb Wave Resonators - Jie Zou; Jiansong Liu; Gongbin Tang (IEEE Access, 2019)
Lamb wave modes with type I dispersion characteristics exhibit strong affinity toward multi transverse modes behavior above resonance frequency (fr) in the AlN Lamb wave resonators (LWRs), especially the high-transduction-efficiency modes: S0 and S1 mode. For conventional interdigital transducer (IDT) design, the IDT aperture and IDT gap are the two main factors impacting the transverse mode placements and strengths, according to the wave vector analysis and finite element method (FEM) simulation. Moreover, the convex slowness curve of the Lamb wave modes propagating in AlN platelets allows the waveguiding and weak lateral leakage into busbars by the high-velocity IDT gap region. Apodization, the standard technique to suppress the transverse modes for IDT-excited resonators, suffers from drawbacks, such as additional loss and reduction of the effective coupling coefficient (keff2). Type I Lamb wave modes in AlN show positive slope in the dispersion branch so that a border region of lower Eigen-resonance frequency is required to form piston mode structure for transverse spurious mode suppression and lateral leakage reduction. Based on dispersion calculations and 2.5D FEM simulations, we demonstrate that by designing the low-velocity border region, such as simply changing the IDT layout, the guiding can be improved and a piston mode can be obtained for the type I Lamb wave modes.